2020
DOI: 10.1017/jfm.2020.455
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on regular reflection of shock wave–boundary layer interactions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The three minimum values ofS MR which fulfil (2.14) for M ∞ = 2, 2.5 and 3 exist at α s = 14.4 • , 16.4 • and 17.1 • , respectively, corresponding to β s = 44.6 • , 38.5 • and 34.5 • . Comparing the three angles to the separation shock angles close to the interaction point of MR measured on the pictures in several recent studies: in the study of Tao et al (2014), the measured angle is β s ≈ 34 • for M ∞ = 3 and in the study of Matheis & Hickel (2015), the measured angles are β s ≈ 41 • for M ∞ = 2 and β s ≈ 34 • for M ∞ = 3; in the study of Grossman & Bruce (2018), the measured angle is β s ≈ 42 • for M ∞ = 2; and in the study of Xue et al (2020), the measured angles are β s ≈ 43 • for M ∞ = 2 and β s ≈ 37 • for M ∞ = 2.5. The comparisons are summarised in table 1.…”
Section: Criteria Considering Viscositymentioning
confidence: 97%
See 4 more Smart Citations
“…The three minimum values ofS MR which fulfil (2.14) for M ∞ = 2, 2.5 and 3 exist at α s = 14.4 • , 16.4 • and 17.1 • , respectively, corresponding to β s = 44.6 • , 38.5 • and 34.5 • . Comparing the three angles to the separation shock angles close to the interaction point of MR measured on the pictures in several recent studies: in the study of Tao et al (2014), the measured angle is β s ≈ 34 • for M ∞ = 3 and in the study of Matheis & Hickel (2015), the measured angles are β s ≈ 41 • for M ∞ = 2 and β s ≈ 34 • for M ∞ = 3; in the study of Grossman & Bruce (2018), the measured angle is β s ≈ 42 • for M ∞ = 2; and in the study of Xue et al (2020), the measured angles are β s ≈ 43 • for M ∞ = 2 and β s ≈ 37 • for M ∞ = 2.5. The comparisons are summarised in table 1.…”
Section: Criteria Considering Viscositymentioning
confidence: 97%
“…Several recent studies (see Matheis & Hickel 2015;Giepman et al 2018;Xue et al 2020) found that the size of the separation bubble is strongly related to the incident shock strength. In the study of Xue et al (2020), it was observed that the separation shock strength close to the interaction point was positively correlated with incident shock, and the separation shock strength in MR was stronger than that in RR, causing difficulty in predicting the RR-to-MR transition. Even though the shock reflection region is so close to the plate leading edge that the boundary layer almost disappears, a separation bubble still exists (see Sriram et al 2016).…”
Section: F (X)mentioning
confidence: 99%
See 3 more Smart Citations